2010
DOI: 10.1371/journal.pcbi.1000933
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Erythrocyte Membrane Protein 1 Diversity in Seven Genomes – Divide and Conquer

Abstract: The var gene encoded hyper-variable Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) family mediates cytoadhesion of infected erythrocytes to human endothelium. Antibodies blocking cytoadhesion are important mediators of malaria immunity acquired by endemic populations. The development of a PfEMP1 based vaccine mimicking natural acquired immunity depends on a thorough understanding of the evolved PfEMP1 diversity, balancing antigenic variation against conserved receptor binding affinities. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
750
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 337 publications
(766 citation statements)
references
References 122 publications
(160 reference statements)
14
750
2
Order By: Relevance
“…Among the different DBL domains characterized, DBLα is the most conserved and is involved in the adherence of infected red blood cells (RBCs) to uninfected RBCs (Chen et al., 1998; Vogt et al., 2003). Bioinformatic analyses have shown that var gene diversity is of ancient origin and maintained by balancing selection, and that through the process of shuffling homology blocks during recombination var genes are able to diversify (Rask et al., 2010; Zilversmit et al., 2013). Moreover, it has been demonstrated that var gene repertoire diversity within and between parasite genomes is also generated by meiosis during sexual recombination (Chen et al., 2011; Zilversmit et al., 2013) and by mitotic recombination during asexual division (Bopp et al., 2013; Claessens et al., 2014; Duffy et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different DBL domains characterized, DBLα is the most conserved and is involved in the adherence of infected red blood cells (RBCs) to uninfected RBCs (Chen et al., 1998; Vogt et al., 2003). Bioinformatic analyses have shown that var gene diversity is of ancient origin and maintained by balancing selection, and that through the process of shuffling homology blocks during recombination var genes are able to diversify (Rask et al., 2010; Zilversmit et al., 2013). Moreover, it has been demonstrated that var gene repertoire diversity within and between parasite genomes is also generated by meiosis during sexual recombination (Chen et al., 2011; Zilversmit et al., 2013) and by mitotic recombination during asexual division (Bopp et al., 2013; Claessens et al., 2014; Duffy et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It also leads to inflammation, occlusion of blood vessels and to the symptoms of severe malaria, including cerebral malaria and pregnancy-associated malaria, which are characterized by marked sequestration of parasites in the brain and placenta [12]. Endothelial tethering is mediated by the P. falciparum erythrocyte membrane protein 1, PfEMP1, a large protein family with ∼60 members encoded in each genome [13,14]. Each PfEMP1 is formed from multiple copies of two parasite-specific domain types, the CIDR and DBL domains, which are most often spatially arranged in a linear array (Figure 1) [15].…”
Section: Do Anti-disease Immunogens Have a Place In Future Malaria Vamentioning
confidence: 99%
“…As proteins that are constantly exposed to the immune system, selection pressure has caused them to expand into a large and antigenically variant protein family that varies significantly between different isolates [13,14]. The population of parasites released from the liver expresses most PfEMP1s, with a reduced repertoire found later in infection [22,23].…”
Section: Do Anti-disease Immunogens Have a Place In Future Malaria Vamentioning
confidence: 99%
See 1 more Smart Citation
“…The studies by Avril et al (1) and Claessens et al (2) identify narrow subsets of group A var genes that were expressed by parasites selected to adhere with high affinity to endothelial cells derived from human brain tissue. When the encoded PfEMP1s were classified according to their domain architecture, they were found to possess one of two specific combinations of binding domain cassettes, referred to as DC8 or DC13, at their N-terminal ends (19). Interestingly, parasites expressing these var genes also bound to endothelial cells derived from nonbrain tissues; however, they did not bind intracellular adhesion molecule 1 (ICAM1), a host surface molecule previously proposed to be the endothelial receptor bound by infected erythrocytes in the brain.…”
mentioning
confidence: 99%